Copper-catalyzed regioselective [3+2] annulation of malonate-tethered acyl oximes with isatins. Issue 27 (8th March 2021) - Duan, Jindian; Mao, Yiyang; Xian, Anmei; Rong, Binsen; Xu, Gaochen; Li, Zhenjiang; Zhao, Lili; Zhu, Ning; Guo, Kai
Abstract : A copper-catalyzed regioselective [3+2] annulation of malonate-tethered acyl oximes with isatins was developed, affording valuable 2, 3-dihydrooxazole-spirooxindoles in moderate to good yields with excellent diastereoselectivity. Abstract : A copper-catalyzed regioselective [3+2] annulation of malonate-tethered acyl oximes with isatins was developed, affording valuable 2, 3-dihydrooxazole-spirooxindoles in moderate to good yields with excellent diastereoselectivity. The reaction sequence involves Cu(i ) initiated N–O bond cleavage, 1, 5-HAT and C–N bond formation. The protocol features mild reaction conditions and broad substrate scope. DFT calculations demonstrated that the [3+2] annulation pathway is more energetically favourable in both kinetics and thermodynamics.